2020
DOI: 10.31557/apjcp.2020.21.10.3077
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relationship between Socio-demographic, Clinical Profile and Financial Toxicity: Evidence from Cancer Survivors in Sarawak

Abstract: Cancer is a chronic disease that exhibits a huge global health concern. According to World Health Organization (2018), cancer accounts for 9.6 million global deaths. It is estimated that one in six deaths is due to cancer. Common cancers worldwide include lung, breast, colorectal, prostate and stomach cancers. In Malaysia, it is estimated that one in four Malaysian is suffering from cancer (Akhtari-Zavare et al., 2018).The five most common cancers include breast, colorectal, lung, lymphoma and nasopharyngeal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…An educational level of less than or equal to 12 years was a significant predictor of higher financial needs, which is similar to the results of our previously studied adult cancer survivors population [13]. Previous reports from the literature also reported unmet needs to be greatest in those with lower educational status, which could be attributed to lower chances of finding good jobs; therefore, as discussed above financial hardships are expected to be higher [26,38].…”
Section: Discussionsupporting
confidence: 88%
“…An educational level of less than or equal to 12 years was a significant predictor of higher financial needs, which is similar to the results of our previously studied adult cancer survivors population [13]. Previous reports from the literature also reported unmet needs to be greatest in those with lower educational status, which could be attributed to lower chances of finding good jobs; therefore, as discussed above financial hardships are expected to be higher [26,38].…”
Section: Discussionsupporting
confidence: 88%
“…Groups at highest risk include new immigrants, visible minorities, those without private health coverage, or those on sick leave. [34][35][36][37][38] In several studies, higher out-of-pocket costs correlated with financial toxicity and decreased treatment adherence. For example, patients with chronic myeloid leukemia in the United States who had higher prescription copayments were almost twice as likely to stop expensive life-prolonging therapy compared with those who had lower copayments, leading to worse outcomes.…”
Section: The Impact On Patients With Cancermentioning
confidence: 99%
“…The latest analysis showed that Malaysia has a UHC effective coverage index higher than the neighbouring countries such as Indonesia, Myanmar and others [56]. Few initiatives were also implemented to reduce the financial barrier to healthcare such as the PeKa B40, mySalam, Bantuan Sara Hidup (BSH) programme, and others which are directly and indirectly cater to the needs of the population to seek healthcare [33]. It is no surprise that the results of the current study showed that the prevalence of distress financing is more concentrated among poor households.…”
Section: Discussionmentioning
confidence: 99%
“…Other medical protection programmes include, but are not limited to; (1) Social Security Organisation (SOCSO) and Employee Provident Funds (EPF), which are two social security funds in Malaysia that provide health coverage for employees working in the private sector; (2) employer insurance scheme, which is provided by some employers in private sectors to their employees; and (3) guarantee letters for the government servants, which allows free health provision among the government servants [32]. Other health financing initiatives provided by the governments for accessing healthcare services include those catered for the bottom 40% of population (B40) groups such as Skim Peduli Kesihatan for the B40 (PeKa B40) and mySalam [33].…”
Section: Introductionmentioning
confidence: 99%